Diffuse pulmonary ossification diagnosed by transbronchial biopsy: A case report. Issue 3 (4th May 2022) - Rodriguez, Teresa; Manos, Daria; Xu, Zhaolin; Houston, Simon
Abstract: Diffuse pulmonary ossification (DPO) is an uncommon but important component of the differential diagnosis for pulmonary calcification in the asymptomatic or minimally symptomatic patient. While surgical tissue biopsy remains the gold standard for histological diagnosis, we present a case illustrating the potential of bronchoscopy with transbronchial biopsy as a less invasive technique for tissue acquisition.